The Economic Integration of Forced Migrants: Evidence for Post-War Germany - Thomas Bauer; Sebastian Braun; Michael Kvasnicka (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2012)
The flight and expulsion of Germans from Eastern Europe during and after World War II constitutes one of the largest forced population movements in history. We analyze the economic integration of these forced migrants and their offspring in West Germany. The empirical results suggest that even a quarter of a century after displacement, first generation migrants and native West Germans that were comparable before the war perform strikingly different. Migrants have substantially lower incomes and are less likely to own a house or to be self-employed. Displaced agricultural workers, however, have significantly higher incomes. This income gain can be explained by faster transitions out of low-paid agricultural work. Differences in the labor market performance of second generation migrants resemble those of the first generation. We also find that displacement considerably weakens the intergenerational transmission of human capital between fathers and children, especially at the lower tail of the skill distribution.
Keywords: J61; O15; R23; 330; Forced Migration; Economic Integration; World War II; West Germany